Использование игровой деятельности для развития внимания у умственно отсталых младших школьников - Шумейко, Т.С.; Герцен, Ю.А. (My University, 2016)
The article deals with features of development of attention in mentally retarded younger pupils. On the basis of theoretical analysis the principles of use of diagnostic games in working with mentally retarded children are revealed . The authors point to the need for connection between the aims of training and playing at the games. In the article there are examples of using games in working with mentally retarded children.
Keywords: the properties of attention; the development of attention; the features of attention of mentally retarded; younger pupils; didactic game; play activity